Dietary Addition of Black Cumin (Nigella Sativa) Seed on the Performance of Broiler Chicken during Summer Season - Devi, N. Sushma; Vidyarthi, V. K.; Zuyie, R. (International Journal of Bio-resource and Stress Management, 2022)
A experiment was conducted with a total number of 120 Cobb-400 strains of broilers were selected and subjected to four dietary treatments with 30 birds each having five replications per treatment. The birds of control group 1were offered standard broiler starter diet till 21 days and thereafter standard finisher diet up to 42 days. The birds of other groups were also offered the same diet as in group 1 along with black cumin seed powder supplementation at the rate of 1.0 (Group 2), 2.0 (Group 3) and 3.0 (Group 4) % of the diet. The values for average body weight, gain in weight, feed consumption,feed conversion efficiency, performance index and carcass weight per bird during the summer season had not shown any impact irrespective of treatments but it had significant (p<0.05) effect on haemoglobin, red blood cells, white blood cells, packed cell volume, low density lipoprotein, high density lipoprotein and Cholesterol. There was no mortality and hence liveability percentage was 100 % in all groups. The dressing percentage, carcass yield and organ weight was found to be best in treatment groups than control. The haematological and biochemical parameters were found to have positive effect in the treatment groups than control. However, the control group had the highest net profit return than treatment groups. Hence, it was concluded that using of black cumin seed as herbal feed additive helps in the improvement of health condition of the birds.